2022
DOI: 10.1177/08944393221131928
|View full text |Cite
|
Sign up to set email alerts
|

The Affiliative Use of Emoji and Hashtags in the Black Lives Matter Movement in Twitter

Abstract: Protests and counter-protests seek to draw and direct attention and concern with confronting images and slogans. In recent years, as protests and counter-protests have partially migrated to the digital space, such images and slogans have also gone online. Two main ways in which these images and slogans are translated to the online space is through the use of emoji and hashtags. Despite sustained academic interest in online protests, hashtag activism, and the use of emoji across social media platforms, little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In digital communication (such as text messaging, email, and social media), emojis reflect the writer’s emotional mood, transmit data, and enable humorous communication without using words, according to the Merriam-Webster online dictionary (2020). Previous studies have shown that emojis are used for various purposes and that different individuals embrace them for a variety of reasons, among which are displaying emotional and social meanings, minimizing ambiguity in communication and seeking changes (Alfano et al, 2022; Kariryaa, Rundé, Heuer, Jungherr, & Schöning, 2022; Kaye et al, 2016). In this sense, emojis may function as a kind of virtual social presence.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In digital communication (such as text messaging, email, and social media), emojis reflect the writer’s emotional mood, transmit data, and enable humorous communication without using words, according to the Merriam-Webster online dictionary (2020). Previous studies have shown that emojis are used for various purposes and that different individuals embrace them for a variety of reasons, among which are displaying emotional and social meanings, minimizing ambiguity in communication and seeking changes (Alfano et al, 2022; Kariryaa, Rundé, Heuer, Jungherr, & Schöning, 2022; Kaye et al, 2016). In this sense, emojis may function as a kind of virtual social presence.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First studies show that social movements strategically use emojis for social distinction and to visually show support for disadvantaged groups (Abbas et al, 2022;Alfano et al, 2022). While conveying emotions quickly and thereby potentially eliciting intentions to engage in collective action, emojis can also backfire.…”
Section: Angermentioning
confidence: 99%